Mitochondrial DNA haplogroups may influence Fabry disease phenotype. (26th August 2016) - Simoncini, C.; Chico, L.; Concolino, D.; Sestito, S.; Fancellu, L.; Boadu, W.; Sechi, G.P.; Feliciani, C.; Gnarra, M.; Zampetti, A.; Salviati, A.; Scarpelli, M.; et al.
Highlights: Mitochondrial impairment and oxidative stress could be implicated in Fabry disease (FD). Haplogroups H and I and haplogroup cluster HV are overexpressed in FD. Detection of haplogroup(s) related oxidative stress requires further investigation. Abstract: While the genetic origin of Fabry disease (FD) is well known, it is still unclear why the disease presents a wide heterogeneity of clinical presentation and progression, even within the same family. Emerging observations reveal that mitochondrial impairment and oxidative stress may be implicated in the pathogenesis of FD. To investigate if specific genetic polymorphisms within the mitochondrial genome (mtDNA) could act as susceptibility factors and contribute to the clinical expression of FD, we have genotyped European mtDNA haplogroups in 77 Italian FD patients and 151 healthy controls. Haplogroups H and I, and haplogroup cluster HV were significantly more frequent in patients than controls. However, no correlation with gender, age of onset, organ involvement was observed. Our study seems to provide some evidence of a contribution of mitochondrial variation in FD pathogenesis, at least in Italy.